Fast dissipative preparation of three-dimensional entangled states for two Rydberg atoms via Lyapunov control - Ding, Zong-Xing; Hu, Chang-Sheng; Shen, Li-Tuo; Su, Wan-Jun; Wu, Huaizhi; Zheng, Shi-Biao (Laser physics letters, 2021)
By using the Lyapunov control approach-an optimization algorithm, we propose a dissipative scheme for efficiently preparing the three-dimensional entangled state of two Rydberg atoms, which subject to Rydberg-Rydberg interactions at the antiblockade regime. The steady target state is the unique dark state of the two-atom system, and is achieved with high fidelity under the Rydberg pumping and the atomic spontaneous emission. The time required to settle into the high-fidelity steady state is greatly accelerated by the help of Lyapunov control, which takes effects while the system is initially prepared in the states containing coherence between the dark state and decoherence-sensitive bright states. The numerical results show that a fidelity of the steady three-dimensional entangled state above 0.99 can be achieved around 2.2 ms with the current experimental conditions. We study in detail the optimal control parameters and show the robustness of the scheme against random noises. The scheme may be generalized for preparation of more complicate multi-atom entangled states.